FENOMENA PENGARUH KUALITAS PRODUK, HARGA, LOKASI, DAN LAYANAN TERHADAP KEPUASAN DAN IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN “HIK”DI KOTA SURAKARTA - Kasidin Kasidin; Sriyanto Sriyanto (Riset Manajemen dan Akuntansi, 2018)
ABSTRACT The research population is customers in the Surakarta city area, from the population randomly taken as many as 130 respondents.The method was used probability sampling.Data collection methods were used interview, questionnaire, and observation.Causal relationships between variables of product, price, location, service and customer satisfaction and their implications for customer loyalty were analyzed using the Structural Equation Modeling (SEM) analysis model.Based on the description of the analysis and discussion can be concluded that 1) Product quality has a positive and significant effect on customer satisfaction in Surakarta City HIK;2) Price has a positive and significant effect on customer satisfaction in Surakarta City HIK;3) Services have a positive and significant effect on customer satisfaction in Surakarta City HIK;4) Satisfaction has a positive and significant effect on the loyalty of the customers of Surakarta City HIK;5) Product quality has a negative and significant effect on customer loyalty in Surakarta City HIK because consumer segment is unique and will have an effect if there is a contribution of satisfaction;6) Price has a positive and significant effect on customer loyalty, instead it contributes to satisfaction in reducing the loyalty of HIK customers in Surakarta City;7) Services have a positive and significant effect on customer loyalty by reinforced customer satisfaction contributions;8) Product quality has an indirect positive effect on loyalty through satisfaction. Keywords: product quality, price, service, satisfaction, customer loyalty